2022
DOI: 10.1177/14550725221110190
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood experiences and neurodevelopmental disorders among youth with and without prenatal substance exposure: A longitudinal matched register-based cohort study

Abstract: Background: Previous research has shown an association between adverse childhood experiences (ACEs) and secondary mental health problems in youth with prenatal substance exposure (PSE), but the association between ACEs and neurodevelopmental disorders is less clear. Methods: This longitudinal register-based cohort study investigated relationships between health at birth, ACEs (out-of-home care (OHC) and maternal adversities), and neurodevelopmental disorders among youth with PSE (alcohol/drugs, n = 615) and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…Conversely, significant and positive associations between ACEs and neurodevelopmental and behavioral disorders have been found, even after adjusting for other covariate factors [ 172 ]. In particular, the association between prenatal alcohol and drug exposure, ACEs, and diagnosed neurodevelopmental disorders has been broadly studied [ 173 , 174 ]. Therefore, the burden of ACEs could be one of the main mediators of the association between NDDs and suicidality.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, significant and positive associations between ACEs and neurodevelopmental and behavioral disorders have been found, even after adjusting for other covariate factors [ 172 ]. In particular, the association between prenatal alcohol and drug exposure, ACEs, and diagnosed neurodevelopmental disorders has been broadly studied [ 173 , 174 ]. Therefore, the burden of ACEs could be one of the main mediators of the association between NDDs and suicidality.…”
Section: Discussionmentioning
confidence: 99%
“…PSE is associated with a complex set of highly interrelated adverse experiences ( Koponen et al, 2020a ), including sexual abuse, as the present study revealed. These traumatic experiences further increase the risk of mental and behavioural disorders, especially attention and conduct problems ( Koponen et al, 2022 ). The results suggest that PSE together with environmental adversities forms the major risk for injuries and poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…Self-assessments of state authenticity – i.e., the experience of being true to oneself in a particular moment – collected from microdosers in the Netherlands indicate that feeling and behaving authentically play a central role in explaining the positive effects of microdosing on health and wellbeing that are reported by current research (Pop & Dinkelacker, 2024). Koponen and colleagues (2024) investigate cumulative risk factors for injuries and poisoning requiring hospital care in youth with prenatal substance exposure. Ruisniemi and colleagues (2024) discuss relational parenthood in addiction recovery and Balbuena and colleagues (2024) bring forth evidence on parental factors predicting social deviance and psychological outcomes in offspring from the Avon Longitudinal Study of Parents and Children (ALSPAC).…”
Section: In This Issuementioning
confidence: 99%